Answer: good luck
Step-by-step explanation:Step 1) Because the first equation is already solved for
y
we can substitute
3
x
+
8
for
y
in the second equation and solve for
x
:
8
x
+
4
y
=
12
becomes:
8
x
+
4
(
3
x
+
8
)
=
12
8
x
+
(
4
⋅
3
x
)
+
(
4
⋅
8
)
=
12
8
x
+
12
x
+
32
=
12
(
8
+
12
)
x
+
32
=
12
20
x
+
32
=
12
20
x
+
32
−
32
=
12
−
32
20
x
+
0
=
−
20
20
x
=
−
20
20
x
20
=
−
20
20
20
x
20
=
−
1
x
=
−
1
Step 2) Substitute
−
1
for
x
in the first equation and calculate
y
:
y
=
3
x
+
8
becomes:
y
=
(
3
⋅
−
1
)
+
8
y
=
−
3
+
8
y
=
5
The solution is:
x
=
−
1
and
y
=
5
or
(
−
1
,
5
)